The Campus Canopy, 1935-01-16 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
Dean's List Posted; Art Club Sponsor; Purples and Reds Tied At Quarter; Audit Privileges Extended to City; S.G.A. Elections; Miss. G.S.W.C. Prefers Emory; New Students this Quarter;
Georgia State Womans College. "The Campus Canopy, January 16, 1935." Vol.01, No.06. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2975. ### Persons Mentioned ### A. D. Corn; A. L. Hunter; Alexa Daley; Alexander Woollcott; Alice Dixon; Alvata Carter; Amanda Barksdale; Amory Mellen; Annette Philips; Annie P. Hopper; Armond Eyler; Arthur Byron; Barbara Stanwick; Ben Stanaland; Bill Tullis; Billy Schroer; Blanche Locklier; Boad Almand; Broun Hutchin; C. W. Beasley; Camille Rogers; Carol Forrester; Carolyn Bullard; Carolyn Green; Carolyn Warnell; Chauncey F. Ryder; Clara Davis Adams; Clark Gable; Clement Greene; Coolidge; Curtis Jack; D. H. Lawrence; Debussy; Denise Beas; Dorothy Ogletree; Dorothy Parker; Dorothy Pittman; J.A. Durrenberger; Earl Phelan; Ed Rivers; Eleanor Miller; Elizabeth McRee; Elizabeth Tudor; Ellie Etheridge; Eloise Ogletree; Esther Smith; Eugene O'Neill; Fletcher; Flora Mitchell; Frances McLain; Frank H. Thomas; Franklin Jennings; Gene Stratton Porter; George Shelton; Geraldine Arrington; Gertrude Gilmer; Gordon Mil; Grace Lahey; Grits Giiffin; Harold Glass; Harold Punke; Harriet Bullard; Harriet Rogers; Harris Dukes; Harry Ulmer; Helen Dale Parrish; Henry Ford; Henry Kate Gardner; Herbert Frasier; Herbert Marshall; Hitler; Hoke S. Dickinson; Huey Long; Ida Lee Stearman; Iva Chandler; J. C. Howell; J. C. Williams; J. D. Ashley; J. E. Martin; J. P. Grace; J. S. Curry; Jac Young; Jack Elliott Howell; James Dasher; Jamie Carroll; Janet Beecher; Jeanette Shifrin; Jeannette Howell; Jerry McRee; Jesslyn Griggs; Jimmie Durante; John D. Paulk; John Gautier; John Sineath; Joseph Ratliff; Joseph Taylor; Josephine Daniel; Joy Miller; Katherine McKenzie; Kathleen Norris; Leila Callender; Leila Urquhart; Leonora DuFour; Lois Dickerson; Lois Pafford; Lora McPhaul; Louelle Giddens; Louise Driskell; Louise Elrod; Louise Hardy; Louise Saw; Louise Sawyer; Lucy Hammond; Margaret Cannon; Margaret Zipplies; Marie Joiner; Marie Rose; Marion Reid; Marshall Paulk; Martha Gardner; Martha Johnston; Mary Agnes Roane; Mary Elizabeth Nix; Mary Nell Carlyle; Mary Polhill; Mary Stuart; Maxwell Anderson; Messrs Jack Howell; Milbrey O'Hara; Mildred Turnbull; Mrs Wesley Odom; Myra Hackett; Myrna Loy; Neal McPhaul; Ola Lee Powell; Pearl Wilson; Permelia Olliff; Roosevelt; Ruby Dillard; Ruth Bunn; Ruth Williams; S. Miller; Sara Norris; Sinclair Lewis; Theo Coleman; Thera Hambrick; Thomas H. Benton; Vangie Trimble; Viola Akins; Virginia Shepherd; Virginia Sineath; W. Harry Griffin; Walt Disney; Walt Williams; Walter Winchell; Wesley Louise Odom; Willa Cather; William B. Hartsfield; William McKay Thomas; Winnie Davis; Za Su Pitts; ### Locations Mentioned ### Albany, Georgia; America; Annapolis, Maryland; Ashburn; Ashley Hall (Valdosta State University); Athens, Georgia; Atlanta, Georgia; Augusta, Georgia; Barnesville, Georgia; Baumstein; West Hall (Valdosta State University); Camilla, Georgia; Carolinas; College Park; Columbia; Columbus, Georgia; Dahlonega, Georgia; Dublin, Georgia; Elberton, Georgia; Emory University; Florida; Fort Pierce, Florida; Gainesville, Georgia; Georgia; Ghent, Belgium; Glenville, West Virginia; Jacksonville, Florida; Jane Street; Kentucky; Key West, Florida; Lake Wales; Lakeland, Georgia; Lebanon; Leesburg; Lohengrin; Macon, Georgia; Maryland; Miami, Florida; Milledgeville, Georgia; Miss Hall; Moultrie, Georgia; Nahunta, Georgia; Nashville; New York; Ocilla, Georgia; Old South; Palm Beach, Florida; Petersburg; Quitman, Georgia; Rocky Mountains; Rossville; Saar Basin; Savannah, Georgia; Scotland; Soperton; South Georgia; Tallahassee, Florida; Tennessee; Valdosta, Georgia; Virginia; Waycross, Georgia; West Point; ### Organizations Mentioned ### American Legion; American Literature; Association of American Colleges; Atlanta Journal; Board of Regents; Sock N Buskin Club; Converse College; Emory University; Fine Arts Club; Georgia Colleges; Georgia Historical Quarterly; Georgia State Womans College; Georgia Tech; Harvard University; Phi Kappa Athletic Association; Philadelphia Society of Etchers; Pine Branch; Princeton University; Reds; Smith Motors; Southern Association of Colleges; Stetson; Turner Jones; Valdosta Club; Valdosta Times; W. S. Quimby Co; Wake Forest University; Wesleyan Advocate; Yale University;
Keywords: College student newspapers and periodicals -- Georgia -- Valdosta; Newspapers; Georgia State Womans College -- Students -- Periodicals